Pengaruh Persepsi Wajib Pajak Tentang Kemudahan, Kegunaan, dan Kepercayaan Terhadap Minat Penggunaan e-filing - Slamet Herutono; Ratna Puji Astuti; Khaidir Ali (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Digitalization in the tax sector has brought significant changes in the services provided to taxpayers. Tax services become faster, more efficient, and accurate. e-Filing is one of the implementations of digital technology in taxation. This research examines the influence of taxpayer’s perceptions of convenience, usefulness, and trust on interest in using e-filing. The location that is the study area for this research is Kantor Pelayanan Pajak (KPP) Pratama Kota Bontang. Sample determination was carried out using a purposive sampling technique with a sample size of 100 respondents. The research results show that taxpayer’s perceptions of usefulness and trustworthiness have a significant influence, while perceptions of convenience do not have a significant influence on interest in using e-filing. However, it is important to ensure that e-filing is easy to use. Simplifying features, reducing unnecessary steps, and providing help (helpdesk) will make it easier for taxpayers to carry out their tax obligations properly